Nutritional information and labels in relation to food advertising: a survey of Macedonian consumers - Suzana Atanasovikj; Ana Marija Kuzmanovska; Tanja Petreska Ivanovska; Zoran Sterjev; Katerina Anchevska Netkovska (Makedonsko Farmacevtski Bilten, 2024)
Food labeling significantly helps consumers to make informed food choices. Considering the importance of nutrition knowledge for using food labels and making dietary decisions, the opinion of consumers on the usage of nutritional information as part of food advertising was investigated. Based on information collected via an online survey of 183 participants in the Republic of North Macedonia, this study provided consumers' perceptions and attitudes regarding food safety, brand influence, health claims, and label comprehensibility. Results of the survey indicated that while a significant percentage of respondents (48.9%) understood health claims, only 26.8% were familiar with the Nutri-Score labeling system. Brand recognition was high (96.1%), with 68.3% associating brand with product quality. Also, concerns about food safety were prevalent, with 64.8% expressing doubts about the safety of food products available at the national market. Another worrying outcome is understanding food labels, since more than half of respondents (58.8%) stated that the labels are not entirely comprehended. This study demonstrated the need for improvement of the public education on labeling systems, enhanced food safety measures, and stated apparent and more readable food labels, ultimately promoting appropriate food choices and ensuring consumer protection in the Republic of North Macedonia.